Sleep disturbances in obese patients with arterial hypertension - O. V. Lubshina; A. L. Vertkin; M. Yu. Maksimova (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To study the sleep structure and sleep disturbances in obese (O) patients with arterial hypertension (AH). Material and methods. Group I included 62 patients (30 women and 32 men) with chronic cerebrovascular disease (CerVD) and arterial hypertension (AH), aged 53,4±7,4 years. Group II included 42 patients (27 women and 15 men) with increased body mass index (BMI), over 30 kg/m2 (mean BMI 33,5±2,6 kg/m2 ), aged 49,3±7,3 years. In all participants, Stage I-II discirculatory encephalopathy was diagnosed. The control group (CG) included 24 healthy volunteers (14 women and 10 men), aged 49,3±8,2 years. Sleep disturbances were evaluated with the questionnaire on subjective assessment of sleep disturbances, as well as with an objective method of polysomnography. Results. Subjective complaints of sleep disturbances were reported by 87% of AH patients. All elements of sleep structure were disturbed: comparing to the CG, falling-asleep time was significantly increased (31,5±9,8 minutes), as well as the prevalence of within-sleep wakefulness (21,1±7,9%; р<0,01). No sleep apnoea symptoms were registered in AH patients. Up to 695 of O patients were not satisfied with their night sleep. Total sleep duration (375±71 minutes) and sleep effectiveness index (80,7±19,2) were decreased. Apnoea index was significantly higher than in the CG: 17,1±9,8 vs. 5,3±1,4, respectively (р<0,001), while saturation parameters were lower than in controls: 84,2±1,4% vs. 96,4±1,1%, respectively (р<0,05). Conclusion. AH patients demonstrated a correlation between sleep disturbances (psycho-physiological insomnia type), psycho-vegetative syndrome severity, and AH severity. In O patients, sleep disturbances were secondary, with the leading role of sleep apnoea.